Effects of distinct Polycystic Ovary Syndrome phenotypes on bone health - Mills, Edouard G.; Abbara, Ali; Dhillo, Waljit S.; Comninos, Alexander N. (Frontiers in Endocrinology, 2023)
Polycystic Ovary Syndrome (PCOS) is a highly prevalent and heterogenous endocrinopathy affecting 5-18% of women. Although its cardinal features include androgen excess, ovulatory dysfunction, and/or polycystic ovarian morphology, women often display related metabolic manifestations, including hyperinsulinaemia, insulin resistance, and obesity. Emerging data reveal that the hormonal alterations associated with PCOS also impact bone metabolism. However, inconsistent evidence exists as to whether PCOS is a bone-protective or bone-hindering disorder with an accumulating body of clinical data indicating that hyperandrogenism, hyperinsulinaemia, insulin resistance, and obesity may have a relative protective influence on bone, whereas chronic low-grade inflammation and vitamin D deficiency may adversely affect bone health. Herein, we provide a comprehensive assessment of the endocrine and metabolic manifestations associated with PCOS and their relative effects on bone metabolism. We focus principally on clinical studies in women investigating their contribution to the alterations in bone turnover markers, bone mineral density, and ultimately fracture risk in PCOS. A thorough understanding in this regard will indicate whether women with PCOS require enhanced surveillance of bone health in routine clinical practice.